Southern Politics Revisited: On V. O. Key's "South in the House". Issue 2 (28th September 2015) - Bateman, David A.; Katznelson, Ira; Lapinski, John
Abstract : V. O. Key's Southern Politics in State and Nation continues to be a central text in political science, the single most important work in understanding the role of the South in American politics. This article returns to, replicates, and seeks to advance Key's analysis of southern politics in Congress, reanalyzing and extending his account of southern strategies and actions in the House of Representatives. Where Key's text was characterized by an episodic attention to issue substance, we focus directly on how southern representation varied across discrete issue areas. We generate temporally fine-grained issue-specific ideal points for members of Congress that allow us to determine how congressional preferences changed across time, generating a more refined portrait of the process by which southern Democratic members diverged from their northern counterparts. We also thicken and extend Key's account along regional and temporal dimensions, assessing how his findings change when we employ a legal-institutional definition of the South, and include the whole period from the beginning of the New Deal to the close of the Truman administration. The article concludes by detailing the significance of our finding to the study of American politics, particularly American political development.